Facile synthesis of Ni-, Co-, Cu-metal organic frameworks electrocatalyst boosting for hydrogen evolution reaction. (10th May 2021) - Zhang, Man; Hu, Di; Xu, Zhenhao; Liu, Biying; Boubeche, Mebrouka; Chen, Zuo; Wang, Yuchen; Luo, Huixia; Yan, Kai
Abstract: The conductive metal-organic frameworks (MOFs) are suggested as the ideal electrocatalysts for hydrogen evolution reaction (HER) because of the high utilization of metal atoms. Rational design and facile synthesis of MOFs with large specific surface area, proper metals as center, and tunable chemical components is still full of challenges. Herein, we report the facile synthesis three types of porous MOFs by regulating metal center using benzene-1, 3, 5-tricarboxylic acid (H3 BTC) as organic ligand and have successfully synthesized the rhombic octahedral Cu-BTC, rod-shaped Co-BTC and spherical Ni-BTC materials with large specific surface area ranged in 350-500 m 2 g −1 . These as-prepared MOFs materials exhibit high performance of HER in 0.5 M H2 SO4 . Ni-BTC material exhibits the lowest overpotential of 53 mV at 10 mA cm -2 and the smallest Tafel slope of 62 mV dec −1 than those of Cu-BTC (270 mV, 155 mV dec −1 ) and Co-BTC (123 mV, 100 mV dec −1 ), which are much superior to these previously reported MOFs catalysts. In addition, the fast catalytic kinetic of Ni-BTC was confirmed by the smaller charge transfer resistance (Rct) value of 0.9 Ω and larger electrochemical active surface area (ECSA) of 35.5 cm 2 than those of Cu-BTC (8.2 Ω, 22.5 cm 2 ) and Co-BTC (1.9 Ω, 27.7 cm 2 ). Because of the structural advantage and large ECSA, the turnover frequency (TOF) value of Ni-BTC reaches up to 0.041 s −1 at 120 mV overpotential, which is 20.5 and 2.6 times greater than that of Cu-BTC (0.002 s −1 ) and Co-BTC (0.016 s −1 ). Besides, these three types of MOFs exhibited excellent durability over 12 h. This study unfolds diverse insights into the design and facile synthesis of MOFs for electrochemical energy conversion system.